Solid state bioconversion (SSB): an effective process for safe disposal and recycling of domestic wastewater sludge as compost - Molla, A. H.; Ahmadun, Fakhru'l-Razi; Alam, Md. Zahangir (Agricultural Society of Sri Lanka, 2006)
The bioconversion or biodegradation of Indah Water Konsortium (IWK) domestic wastewater treatment plant (DWTP) sludge was evaluated using two-screened compatible mixed filamentous fungi, Trichoderma harzianum Rifai with Phanerochaete chrysosporium 2094, and T. harzianum with Mucor hiemalis Wehmer, by exploiting the technique of Solid State Bioconversion (SSB). It was done to evaluate the feasibility of SSB process for ultimate safe, environmental friendly and non-hazardous disposal of wastewater sludge. The process could offer environmentally friendly and non-hazardous ultimate disposal technique of wastewater sludge by ensuring the value added end product in a comparatively short period of time. The obtained results on germination index (GI), total organic carbon (TOC), electrical conductivity (EC) and E4/E6 ratio of humic & fulvic acids were clearly implied the significant biodegradation of DWTP sludge. The reduction of heavy metals was the results of dilution effect of the SSB process that ensured the most non-hazardous avenue of economic use of wastewater sludge. The comparisons of the composts obtained by SSB process with standard (based on determining factors of quality composts) further ensured its safe disposal and recycling. However, the adopted biological process might be considered as the most useful and convenient way of sludge management and disposal than any other conventional techniques. The SSB process, a noble natural biological and effective technique might address a sound direction for bioremediation, safe disposal and recycling of contaminated wastes.